Increasing of oral health education knowledge after intervention psychoeducation methods in adolescents - Yubiliana, Gilang; Kusumah, Salsabila Putri; Abdurrochman, Andri (Universitas Padjadjaran, 2023)
ABSTRACT Introduction: The technique of imparting knowledge and understanding known as